Suppressed Expression of T-Box Transcription Factors Is Involved in Senescence in Chronic Obstructive Pulmonary Disease - Acquaah-Mensah, George K.; Malhotra, Deepti; Vulimiri, Madhulika; McDermott, Jason E.; Biswal, Shyam (PLOS Computational Biology, 2012)
Author Summary Chronic obstructive pulmonary disease or COPD is among the most lethal of respiratory diseases. While this disease has been well characterized, more studies are needed to learn the interaction of macromolecules involved in the progression towards illness. We explored possible interactions involved in the disease process using a compendium of gene expression data from frontline cells of the respiratory airways of the lung. The gene expression data were generated under a variety of experimental conditions. Application of computational schemes, which robustly detect enduring patterns, among sections of the genes represented across the varying experimental perturbations, revealed important regulatory relationships. When gene expression data from lungs of patients with COPD were factored into these networks of regulatory relationships, certain highly connected nodes (hubs) representing differentially expressed genes emerged. Notably included are members of the T-box (TBX) family of genes and CDKN2A, which regulate cellular aging. These findings were confirmed in studies using lung samples from COPD patients. Novel genes linked to TBX and CDKN2A include COL4A3, CFLAR, GULP1, PDCD1, CASP10, PAX3, BOK, HSPD1, PITX2, and PML, which were thus predicted to be involved in the disease process. The balance between senescence and anti-senescence factors is disrupted towards senescence in COPD lungs.